Overcoming information asymmetry in tourism carbon management: The application of a new reporting architecture to Aotearoa New Zealand. (April 2021) - Sun, Ya-Yen; Higham, James
Abstract: Responding to the United Nations Sustainable Development Goals and Paris Climate commitments are urgent priorities facing many governments. Meeting these commitments will require new industry management architectures that align measures of progress (economic, environmental, human and social) with government structures, datasets, and reporting. Comprehensive emissions quantification and reduction targets for tourism must be a part of this new architecture. In this paper we propose a comprehensive Tourism Carbon Information System (TCIS), comprising four essential information components: national tourism carbon footprint, the carbon-economic linkage, drivers and decarbonization progress, and benchmarking. The TCIS is then tested and applied to Aotearoa New Zealand (2007–2013) to track tourism carbon performance and its decarbonization speed, compared to the national average across sectors. This critical information sheds light on future growth in tourism relative to the national greenhouse gas inventory and establishes the required mitigation trajectory for destinations to move onto a sustainable emissions pathway.